Direct Lineage Reprogramming: Harnessing Cell Plasticity between Liver and Pancreas - Ruzittu, Silvia (Cold Spring Harb Perspect Biol, 2020)
Direct lineage reprogramming of abundant and accessible cells into therapeutically useful cell types holds tremendous potential in regenerative medicine. To date, a number of different cell types have been generated by lineage reprogramming methods, including cells from the neural, cardiac, hepatic, and pancreatic lineages. The success of this strategy relies on developmental biology and the knowledge of cell-fate-defining transcriptional networks. Hepatocytes represent a prime target for β cell conversion for numerous reasons, including close developmental origin, accessibility, and regenerative potential. We present here an overview of pancreatic and hepatic development, with a particular focus on the mechanisms underlying the divergence between the two cell lineages. Additionally, we discuss to what extent this lineage relationship can be exploited in efforts to reprogram one cell type into the other and whether such an approach may provide a suitable strategy for regenerative therapies of diabetes.